2021
DOI: 10.3389/fmed.2021.678434
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Risk Factors Associated With Acute Kidney Injury Inpatient With Exertional Heatstroke: An Over 10-Year Intensive Care Survey

Abstract: Background: Exertional heat stroke (EHS) is a life-threatening injury that can lead to acute kidney injury (AKI). The clinical characteristics of and risk factors for EHS complicated with AKI have been poorly documented.Methods: A retrospective study with EHS admitted to the intensive care unit (ICU) from January 2008 to June 2019 was performed. Data including baseline clinical information at admission, main organ dysfunction, 90-day mortality and total cost of hospitalization were collected.Results: A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Indeed, patients diagnosed with heatstroke often suffer from acute kidney injury (e.g., Gauss and Meyer, 1917; Kew et al., 1967; Schrier et al., 1970), characterized by elevations in serum creatinine, which is indicative of reductions in glomerular filtration rate, measured as part of the basic clinical bloodwork (Ward et al., 2020). A recent analysis of 187 EHS cases in southern China identified that ∼44% of patients developed acute kidney injury and that ∼27% of the patients with acute kidney injury died within 90 days (Wu et al., 2021). Thus, the management of acute kidney injury following the diagnosis of heatstroke is an essential consideration.…”
Section: Kidneysmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, patients diagnosed with heatstroke often suffer from acute kidney injury (e.g., Gauss and Meyer, 1917; Kew et al., 1967; Schrier et al., 1970), characterized by elevations in serum creatinine, which is indicative of reductions in glomerular filtration rate, measured as part of the basic clinical bloodwork (Ward et al., 2020). A recent analysis of 187 EHS cases in southern China identified that ∼44% of patients developed acute kidney injury and that ∼27% of the patients with acute kidney injury died within 90 days (Wu et al., 2021). Thus, the management of acute kidney injury following the diagnosis of heatstroke is an essential consideration.…”
Section: Kidneysmentioning
confidence: 99%
“…of the patients with acute kidney injury died within 90 days (Wu et al, 2021). Thus, the management of acute kidney injury following the diagnosis of heatstroke is an essential consideration.…”
Section: Kidneysmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports have suggested that advanced age, disturbed consciousness, elevated serum creatinine (Cre) and total bilirubin (T-bil) levels, and coagulation disorder are risk factors for death 2 , 3 . In reports that focused on exertional heatstroke, acute kidney injury 4 and myocardial injury 5 were identified as risk factors. Other groups have also developed a scoring system (exertional heat stroke score [EHSS]) for classifying the severity of exertional heatstroke 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also shown that RM caused by heatstroke may be an important factor in initiating sepsis (2)(3)(4)(5)(6) and will further cause the disturbance of blood coagulation, which can easily lead to the occurrence of DIC (7) and AKI (8,9). Research showed that the Sequential Organ Failure Assessment (SOFA) score was an independent risk factor affecting the survival of patients (10); therefore, treatments based on reducing the SOFA score may be pivotal for reducing the mortality of EHS complicated with AKI (11). However, so far there are few clinical studies on the clinical characteristics and prognosis of EHS complicated with RM, and there is no scoring system that can predict prognosis in patients with RM with EHS.…”
Section: Introductionmentioning
confidence: 99%